A PROCEDURE TO TEACH SELF-CONTROL TO CHILDREN WITH ATTENTION DEFICIT HYPERACTIVITY DISORDER - Binder, Lisa M.; Dixon, Mark R.; Ghezzi, Patrick M. (Journal of applied behavior analysis, 2000)
This study examined the use of a progressive delay procedure combined with verbal mediation to teach self‐control to children with attention deficit disorder. Results showed that when participants were initially given the choice between an immediate smaller reinforcer and a larger delayed reinforcer, all participants chose the smaller reinforcer. When slight delays to obtain a larger reinforcer were instated in conjunction with intervening verbal activity, all participants demonstrated self‐control regardless of the content of the verbal activity.